Novel FPGA-based Instrumentation for Personnel Safety Systems in Particle Accelerator Facility. (November 2019) - Pioli, S.; Frasciello, O.; Beretta, M. M.; Ciambrone, P.; Di Giulio, C.; Buonomo, B.; Belli, M.; Valente, P.; Variola, A.
Abstract: Personnel Safety System for particle accelerator facility involves different devices to monitor gates, shielding doors, dosimetry stations, search and emergency buttons. In order to achieve the proper reliability, fail-safe and fail-proof capabilities, these systems are developed compliant with safety standards (like the IEC-61508 on "Functional Safety", ANSI N43.1 "Radiation Safety for the design and operation of Particle Accelerator" and NCRP report 88) involving stable technologies like electro-mechanical relays and, recently, PLC. As part of the Singularity project at Frascati National Laboratories of INFN, this work will report benchmark of a new FPGA-based system from the design to the validation phase of the prototype currently operating as personnel safety system at the Beam Test Facility (BTF) of Dafne facility. This novel instrument is capable of: devices monitoring in real-time at 1 kHz, dual modular redundancy, fail-safe and fail-proof, multi-node distributed solution on optical link, radiation damage resistance and compliant with IEC-61508, ANSI N43.1 and NCRP report 88. The aim of this FPGA-based system is to illustrate the feasibility of FPGA technology in the field of personnel safety for particle accelerator in order to take advantage of a fully digital system integrated with facility control system, evaluate the related reliability and availability and realize a standard, scalable and exible hardware solution also for other fields with similar requirements like machine protection systems.